Editorial - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2015)
With the present issue, Studies in Second Language Learning and Teaching enters the fifth year of its existence, a year that has already started on a very positive note as the journal has just been included in the European Reference Index for the Humanities (ERIH PLUS). This, as well as the fact that SSLLT has been indexed or abstracted in other prestigious databases, constitutes tangible proof of the growing recognition that it has been gaining in the field. It is also likely to contribute to a considerable increase in the number of citations, something that we need really badly if we want to have the journal listed by the Thomson Reuters Master Journal List. This is certainly a goal that we will be vigorously pursuing and I am confident that we will be able to accomplish it in the near future. Obviously, the number of citations depends in the main on the quality of the papers published because only the best ones stand the chance of being referred to by other specialists, particularly those who routinely publish their work in the most prestigious journals in the field. We are doing our best to ensure the highest possible quality of the papers that appear in SSLLT and one way to do it is to invite renowned scholars as guest editors of thematic issues. This is exactly what is going to happen this year since Sarah Mercer and Stephen Ryan have kindly agreed to put together two issues of the journal which will include papers based on presentations delivered during the first conference on psychology and language learning, which was held in Graz in May, 2014. The line-up of contributors to these two issues is really impressive and they will surely be a real treat for our readers. This is by no means to suggest that the papers included in the regular editions are any less valuable or engaging, as amply demonstrated by the present one.